1998
DOI: 10.1021/js970179k
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Oxymoron: Concentration-Dependent First-Order Rate Constants for Hydrolysis of Ceftazidime

Abstract: The influence of pH, temperature, and buffers on the hydrolysis of 10(-4) M ceftazidime was previously reported. The pH-rate profiles showed that maximum stability occurred in the pH-independent region from 4.5 to 6.5. In the present study, hydrolysis rates of 0.031, 0.14, 0.25, and 0.35 M ceftazidime were measured at 30 and 65 degrees C, pH 5.5-6.2. The data were consistent with beta-lactam hydrolysis and the rapid release of pyridine. The sum of the time-dependent concentrations of ceftazidime and pyridine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Mass spectrometry data indicated that degradation of cefepime includes cleavage of N-methylpyrrolidine (R2 side chain) and opening of the cephem (␤-lactam ring). This was the expected breakdown of cefepime, since two related compounds, ceftazidime and cefpirome, have shown similar breakdown (5,11). It also indicates that the ring opening occurs before the cleavage of N-methylpyrrolidine.…”
mentioning
confidence: 60%
“…Mass spectrometry data indicated that degradation of cefepime includes cleavage of N-methylpyrrolidine (R2 side chain) and opening of the cephem (␤-lactam ring). This was the expected breakdown of cefepime, since two related compounds, ceftazidime and cefpirome, have shown similar breakdown (5,11). It also indicates that the ring opening occurs before the cleavage of N-methylpyrrolidine.…”
mentioning
confidence: 60%
“…Pyridine is formed quantitatively from the degradation of ceftazidime in buffered aqueous solutions (13). In the present study, the mass of pyridine produced was close to the theoretical values, with a reduction to around 95% after 14 days at 7 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were made for other antibiotics. For example the hydrolysis of ceftazidime is self-accelerated at higher concentration because ceftazidime and its decomposition product act as similarly strong general-base catalysts, 13 and the authors concluded that all antibiotics which are sensitive to general acid-base catalysis and contain functional groups such as amino-or hydroxyl groups, which can act as such catalysts, are likely to selfcatalyze their own decomposition. Indeed, the isomerisation of ceftibuten is facilitated by itself as a general acid or base catalyst, 14 so is the hydrolysis of amoxicillin by the catalytic action of the phenolic hydroxyl group 15 and the degradation of imexon.…”
Section: Discussionmentioning
confidence: 99%